Jogos cognitivos controlados por interface cérebro-computador: desenvolvimento e avaliação dos impactos na atenção e aprendizagem de estudantes do ensino fundamental anos iniciais - Azevedo, Paulo Cesar Viana (2025)
The difficulty of students in maintaining attention during the learning process is considered one of the factors that can generate unsatisfactory learning and, often, cause impacts that reflect in various aspects of their daily lives. The present study aimed to evaluate the impacts of two cognitive games controlled via Brain-Computer Interface, developed to assist in the improvement of attention and learning of students in the early years of elementary education. The referred study is characterized as field research, descriptive and with a mixed approach (qualitative-quantitative), conducted over six months in a private school in the city of Fortaleza, in the State of Ceará. The sample was composed of six students, aged between 8 and 10 years, and to be included in the sample, the students had to sign the Free and Informed Assent Form, in addition to the signing of the Free and Informed Consent Form by their guardians. Before the training sessions, the main researcher had a conversation with the students’ teachers to obtain detailed information about their school difficulties, attention levels, and any pre-existing diagnosis of conditions such as Attention Deficit Disorder, Autism, or any other disorder or syndrome. The training procedures were also explained to the guardians in a meeting, including its objectives, the nature of the activities involved, in addition to the expectations regarding the students’ participation. The referred study was developed through training lasting 6 months with games controlled by Brain-Computer Interface. The training consisted of two weekly sessions, with an average duration of 20 minutes. In the end, 40 sessions and a total of 800 minutes were recorded, equivalent to 13h and 20 minutes of games. While some students played more, others played less than this time. The research met all the criteria of the Ethics Committee on research involving human beings. To analyze the quantitative data, a mixed statistical model with a random intercept was used. The results revealed a general increase in the students’ average attention, with significant individual variations. The participants were divided into three groups: (1) statistically significant improvement (p<0.05) (Participants 1 and 6); (2) positive trend, but without statistical significance (p>0.05) (Participants 2 and 4); and (3) no significant variations (p>0.05) (Participants 3 and 5). The modeling with mixed models confirmed the reliability of the data from this study, highlighting that individual factors such as motivation and learning pace can directly influence the results. The intervention proved to be effective in improving attention, especially in students with some attentional control, but it is suggested that it be combined with other strategies or longer training periods for cases in which no significant improvement was obtained. It is concluded that training with cognitive games can promote improvements in attention, learning, and socioemotional development of students, especially those with Attention Deficit Hyperactivity Disorder and Autism Spectrum Disorder, in addition to advances in subjects such as mathematics and science. Although the technology presents potential as a pedagogical tool, its access is still limited and restricted to specific contexts. Therefore, it is recommended to carry out studies with games controlled via Brain-Computer Interface in different educational contexts and age groups, with the aim of expanding inclusion and personalized teaching, seeking to overcome current accessibility barriers.